Functional alteration of divided attention in people living with HIV based on a task-fMRI study - Chen, Junzhuo; Guan, Zhongtian; Hou, Chuanke; Jiang, Xingyuan; Luo, Haixia; Xu, Fan; Li, Aixin; Wang, Xi; Wang, Wei; Li, Chunlin; Li, Hongjun (Frontiers in Neuroscience, 2026)
BackgroundImpaired attention is a key feature of HIV-associated brain damage, and people living with HIV (PLWH) often have potential visual–auditory perceptual deficits. This study aimed to explore functional alterations in divided attention in PLWH using a parallel audio-visual spatiotemporal task with multimodal functional magnetic resonance imaging (fMRI) and to explore candidate neuroimaging markers of HIV-related attention impairment.MethodsThirty-one cognitively unimpaired PLWH and 34 healthy controls (HC) completed a divided attention task during fMRI via a modified Posner paradigm. Behavioral performance and task-related brain activation were compared between the two groups. Seed-based whole-brain functional connectivity (FC) maps were computed in resting-state fMRI (rs-fMRI) using a priori anatomical regions of interest (ROIs) from the audiovisual attention network, defined based on previous independent fMRI studies employing similar spatial–temporal attention paradigms.ResultsThe PLWH showed lower accuracy than HC. Task-related brain activation was more extensive in PLWH, including increased activation in occipital/temporal lobes, plus frontal/parietal lobes, insula, and limbic system. Using a priori anatomical regions of interest from the audiovisual attention network as seeds, PLWH exhibited increased resting-state FC between these frontal–parietal–temporal–insular regions and bilateral posterior cerebellar lobules VIII–IX, as well as with multimodal associative cortices. Within the PLWH group, percent BOLD signal change showed significant positive correlations with HIV infection duration in a subset of task-difference ROIs—7 regions identified under spatial cueing and 13 regions identified under temporal cueing.ConclusionThe HIV impairs audio-visual divided attention, with fMRI revealing neural alterations in cognitively unimpaired PLWH. These findings suggest that task-related activation patterns and resting-state connectivity measures may serve as sensitive candidate markers of HIV-related brain involvement and help identify individuals at increased risk of cognitive decline, although longitudinal studies are needed to establish their prognostic value.